PENGEMBANGAN BUKU CERITA BERBANTU PENDEKATAN WHOLE LANGUAGE UNTUK MEMFASILITASI KETERAMPILAN MEMBACA ANAK USIA DINI - Wahyuni, Teti; Elan, Elan; Sumardi, Sumardi (JURNAL PAUD AGAPEDIA, 2021)
The aim of this research is to find out the basic needs for developing storybooks with the help of a whole language approach to facilitate early childhood reading skills. The researcher uses the development method, the mix method approach model with the Educational Design Research technique refers to the model according to McKenney and Reeves. The discussion in this article only describes the Educational Design Research technique research in the first stage, namely the exploration and analysis stage of the research problem. The data collection stage is carried out by conducting a preliminary study, namely field studies and literature studies. Field studies or initial observations were carried out in Kober Ceria, Cibeureum District, Tasikmalaya City. The literature study was conducted by reviewing journals and the results of previous research related to problems and books on language development in early childhood. The results of the study show various basic needs to develop storybooks with the help of a whole language approach to facilitate early childhood reading skills, this will be used as a guide in making product designs for developing storybooks with the help of a whole language approach.Penelitian yang dilakukan bertujuan untuk mengetahui dasar kebutuhan pengembangan buku cerita berbantu pendekatan whole language untuk memfasilitasi keterampilan membaca anak usia dini. Peneliti menggunakan metode pengembangan, model pendekatan mix method dengan teknik Educational Design Research mengacu pada model menurut McKenney dan Reeves. Bahasan dalam asrtikel ini hanya menjelaskan penelitian teknik Educational Design Research pada tahap pertama yaitu tahap eksplorasi dan analisis masalah penelitian. Tahap pengumpulan data dilakukan dengan melakukan studi pendahuluan yaitu studi lapangan dan studi literatur. Studi lapangan atau observasi awal dilaksanakan di Kober Ceria Kecamatan Cibeureum Kota Tasikmalaya. Studi literatur dilakukan dengan mengkaji jurnal dan hasil penelitian terdahulu terkait permasalahan serta buku-buku tentang perkembangan bahasa pada anak usia dini. Hasil penelitian menunjukan berbagai kebutuhan dasar untuk mengembangkan buku cerita berbantu pendekatan whole language untuk memfasilitasi keterampilan membaca anak usia dini, hal ini akan dijadikan sebagai pedoman dalam pembuatan rancangan produk pengembangan buku cerita berbantu pendekatan whole language.